The CAPM is Wanted, Dead or Alive - FAMA, EUGENE F.; FRENCH, KENNETH R. (Journal of Finance, 1996)
ABSTRACT Kothari, Shanken, and Sloan (1995) claim that β s from annual returns produce a stronger positive relation between β and average return than β s from monthly returns. They also contend that the relation between average return and book‐to‐market equity (BE/ME) is seriously exaggerated by survivor bias. We argue that survivor bias does not explain the relation between BE/ME and average return. We also show that annual and monthly β s produce the same inferences about the β premium. Our main point on the β premium is, however, more basic. It cannot save the Capital asset pricing model (CAPM), given the evidence that β alone cannot explain expected return.